Detection of B lymphocytes in the central nervous system of cattle and horses naturally infected with rabies virus - Achkar, S. M.; Fernandes, E. R.; Carrieri, M. L.; Duarte, M. I. S. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Humoral immunity has an essential protective function in the course of rabies virus infection. Virus-neutralizing antibodies, under the control of T helper cells, play a critical role in immunoprotection. Therefore, our aim was to detect the presence of B lymphocytes in samples of central nervous system (CNS) from cattle and horses and compare the findings between species. For this were selected four samples of cattle and four samples of horses. Fragments CNS (cortex, hippocampus, cerebellum and brain stem) were analyzed by immunohistochemical reaction. All immunostained cells were quantified with the aid of the graticule of 1 cm2 coupled in light microscope with 10x eyepiece and 40 x objective, were quantified 40 fields in every fragment of the CNS. Results were expressed in number of cells per mm2. When comparing the population of B lymphocytes in cattle and horses, we found a statistically significant increase of these cells in cattle in relation to horses (p = 0.0006). By analyzing c rmv s p . g o v . b r mv&z 69 the different brain areas in samples obtained from bovine not was found statistically significant differences between areas, but in samples of horses was found a greater presence of these cells in the brain stem (p = 0.0266). We could also observe that the meningeal and perivascular environments were where we find more immunostaining for B lymphocytes. The detection of B lymphocytes in CNS samples of cattle and horses was more pronounced in meningeal and perivascular environments, suggesting that these cells would be entering the CNS by breaking the blood brain barrier, however, the induction of specific antibodies for viral clearance is delayed, occurring only when the animal already have in severe neuronal damage. Although we have detected B cells in situ in the samples studied, these cells were in small amounts mainly in samples of horses. The collaboration intercellular between CD4 + T lymphocytes and B lymphocytes for activation of these cells and consequently induction of specific antibodies to the virus may be impaired because CD4 + T lymphocytes when entering the CNS may undergo apoptosis through its association with infected neurons that up expressing FASL and bind to CD4 + T cells expressing FAS occurring so the death of these immune cells essential for protection against rabies virus. These findings are important for understanding how the immune response is manifested in these animal species and also to improve understanding of the pathogenesis of rabies in cattle and horses.